#TITLE_ALTERNATIVE# - KETUT ARIESKA P. K. (NIM 10103069), NI
This final project studies mathematical model for population growth of HIV in the human body. Using this model and specific parameters chosen, we can show that HIV which infect T cells decreases the number of T cells in the blood until a certain value which is about 200 cells/mm3. In reality, as time goes by, a person who has been infected with HIV is likely to become ill more and more often until, usually several years after infection, they become ill with one of a number of particularly severe illnesses. It is at this point that they are said to have AIDS, when the number of immune system cells left in their body drops below a certain value. This final project also discusses mathematical model for an HIV infection with mutations. From the model we get a number Ndiv. This represent the number of mutations that can be accomodated before the immune system collapses. The simulation of this model confirm this.